Qur’anic Interpretation among Sasak Muslims across Communities, Theologies, and Ideological Conflicts - Muhammad Taufiq; Muhammad Said (UIN Sunan Kalijaga Yogyakarta, 2025)
The Sasak Muslim community in Lombok, Indonesia has a long history of interpreting the Qur’an in ways that reflect their unique social and cultural setting—especially through oral traditions and communal religious practices that date back to the 16th century. Despite this, most studies on Islam in Lombok have focused mainly on rituals, teachings, or the sociocultural differences between Islam Wetu Telu and Waktu Lima. What often gets overlooked is how these communities actually make sense of the Qur’an, and how their interpretations influence their religious identity or even contribute to tensions between groups. This study addresses that gap by looking closely at how Qur’anic interpretation works on the ground among Sasak Muslims. Using a qualitative approach—through field observations, in-depth interviews, and document analysis—this research explores how different forms of tafsir have emerged within the Wetu Telu and Waktu Lima communities. It finds that Wetu Telu Muslims built their religious identity through oral interpretation, delivered by early preachers in simple, local language during the initial spread of Islam in Lombok at the end of the 16th century. Their approach tends to be flexible, adapting Qur’anic teachings to local traditions and values. In contrast, Waktu Lima Muslims developed a more textual and orthodox form of tafsir, rooted in classical Arabic commentaries brought home by Sasak scholars (tuan guru) who studied in the Middle East. They institutionalized this knowledge in pesantren, turning them into canters of formal Islamic learning. This study contributes to the growing field of tafsir studies by expanding the focus beyond written texts, showing that interpretation can also be oral, social, and embedded in everyday religious life. By comparing local and textual models of tafsir, this research offers a new way to understand how the authority of interpretation is shaped—and contested—within the diverse landscape of Indonesian Islam.